The recovery management of patients with operated extrame-dullary spinal arteriovenous fistula, evolution and socio-professional reintegration: case report and review of the litera-ture (Balneo and PRM Research Journal, 2022)
ABSTRACT: Adequate therapeutic intervention performed in the case of extradural spinal AVM and an intensive recovery program allow the amelioration of neurological manifestations in a very high percentage. With the ultimate goal of practicing a trade, a good biological recovery is needed for social recovery. The effectiveness of strategies for professional integration and reintegration depends largely on the patient’s experiences before the onset of the disease. The paper aims to review the treatment, the evolution of patients with extradural spinal AV and the possibilities of socio-professional reintegration. Methods and analysis. A case presentation of a patient diagnosed with extradural spinal AV fistula is proposed, along with a review of the current literature on the treatment of this pathology, the evolution and the possibilities of vocational recovery. The studies will be analysed and selected in two stages, in the first stage the titles and abstracts, in the second stage, the articles with full text will be analysed, selected and a narrative synthesis of the included studies will be made. Summary case. The 51-year-old urban patient, a professional driving instructor who underwent endovascular and surgical treatment for extradural spinal AV fistula, is hospitalized for a moderate motor deficit, such as paraparesis, back pain, mechanical pain in the knees and gait disorders. The objectives of recovery are represented by neuromotor recovery and socio-professional reintegration. Conclusions. Spinal EAVFs are rare lesions with a low risk of bleeding; the clinical manifestations are determined by the compression of the bone marrow; these being significantly improved after the endovascular and surgical treatment. Studies show a good long-term prognosis, which is determined by the absence of recurrences. An essential role in the integration of patients with disabilities in the socio-professional life is the identification of their deficiencies and their reorientation according to the outstanding abilities, the stimulation of the preserved skills.Keywords: rehabilitation, disc hernia, low back pain, paraplegia